(untitled) (Journal of Educational Sciences, 2016)
Principles of designing academic strategies of universities are defined, their general characteristics is given. The article considers the principles of research, intellectual and innovative universities. We are focusing attention on the network structure of the constructing management in innovative or entrepreneurial university. We consider the theory of meritocratic education. Technological level of academic strategies design – principles of consistency, variability, complexity of the design and application of uniform design standards– are defined. They are derived from innovation management. Additionally system design principles: the practical utility, the unity of components, the variability in time – are introduced. The purpose of this design is conforming to the megatrends of development of modern education and to the principles of the educational policy of the state and the university.